Monitoramento e processamento de sinais no processo a laser de cerâmicas avançadas - Andrade, Ana Carolina Balarin de [UNESP] (Universidade Estadual Paulista (Unesp), 2021)
Este trabalho propõe uma nova técnica de monitoramento na usinagem a laser de cerâmicas avançadas. As cerâmicas avançadas possuem dentre as suas principais propriedades mecânicas alta dureza e resistência, porém essas propriedades acabam dificultando a sua usinagem em métodos convencionais. Nesse sentido, a usinagem a laser é apresentada como uma alternativa aos métodos convencionais, além de permitir uma usinagem mais precisa. Assim sendo, são necessários sistemas de monitoramento em tempo real para otimizar a usinagem a laser em cerâmicas e este trabalho propõe um novo método para o monitoramento do processo de marcação a laser em uma peça de alumina usando um transdutor piezoelétrico de baixo custo e processamento digital de sinais. No decorrer do trabalho, foram realizados testes considerando variáveis que influenciam diretamente na usinagem a laser, como a potência e a velocidade de varredura do laser. Os resultados do processamento digital mostraram uma correlação bastante satisfatória com as condições de usinagem utilizadas, no qual os sinais apresentaram uma maior atividade acústica em marcações que ocorreram mais ablação e danos, enquanto que a atividade acústica foi menor em marcações com menos danos e ablação. Por meio dos resultados foi possível também demonstrar que há uma boa sensibilidade à atividade acústica do transdutor piezoelétrico de baixo custo, o que permite o seu uso com eficiência no monitoramento do processo de marcação a laser de alumina.

This work presents a new method of monitoring advanced ceramics in laser process machining. Advanced ceramics, due to their particular properties, are widely used in industry. However, the machining of ceramics by conventional methods is difficult due to its high level of hardness and brittleness. In this sense, laser machining emerges as an alternative to traditional methods, and in turn real-time monitoring systems are needed to optimize laser machining in ceramics. Thus, this work proposes a new technique for monitoring the laser grooving process of ceramic components using a low-cost piezoelectric transducer and digital signal processing. Tests were performed during the research, in which variables that directly influence laser machining were considered, such as laser power and scanning speed. Adopting the selected machining conditions, a low-cost piezoelectric transducer was used as an acoustic emission sensor and the signals from the laser grooving process were collected at a sampling rate of 2MHz. Time-domain and frequency domain analyses were performed, applying RMS statistics, the mean values and standard deviation, and the FFT, to find a frequency band that best correlates with the process conditions. The mechanical characterization was carried out through tests using a digital microscope, optical microscope, and optical profilometer to obtain the widths and depths values of the grooves resulting from laser grooving. The digital processing results present a satisfactory correlation between the signals and the machining conditions used, which showed higher acoustic activity in grooves with a higher material removal and damage, whereas grooves with minor damage and less laser ablation showed a lower acoustic activity. The results also showed that the low- 9 cost piezoelectric transducer was sensitive to the acoustic activity generated during the process, allowing the real-time monitoring of the laser grooving process in the alumina piece
Monitoring and Digital Signal Processing in Advanced Ceramics Laser Process
Keywords: Processamento de sinais - Tecnicas digitais; Cerâmicas; Usinagem; Usinagem a laser; Cerâmicas avançadas; Laser machining; Ceramic; Piezoelectric transducers; Monitoring; Digital signal processing